Impact of therapeutic gardens on the quality of life of the elderly: Chorrillos case – Lima - Peru - Chavez Florián, César (2024)
The research addresses population aging and the lack of adequate infrastructure to improve the quality of life of the elderly in Chorrillos, Lima. The objective is to analyze the impact of therapeutic gardens on this population, exploring the natural environment, health and well-being benefits, and the design principles of therapeutic gardens. The study examines how physical, interpersonal, and emotional dimensions’ influence quality of life. Using a descriptive and qualitative methodology, observation forms, analogous cases, and expert interviews are employed. The results show that therapeutic gardens in Chorrillos contribute to improving mobility, reducing stress and promoting socialization among older adults, benefiting them physically and emotionally, especially in people with senile dementia and chronic diseases.